HUBUNGAN KESEHATAN MENTAL SISWA TERHADAP HASIL BELAJAR PJOK DI SMP NEGERI 2 TORJUN - Fadia Syafaril Effendy; Anung Priambodo (STAND, 2023)
The purpose of this study was to determine the relationship between students' mental health and PJOK learning outcomes at SMP Negeri 2 Torjun. This type is quantitative with correlational method. This research is a population study in which all populations are used as a sample of 75 students. The instrument used was a mental health questionnaire, while in analyzing the data used was correlational. Based on the results of the study, there is a relationship between mental health and PJOK learning outcomes at SMP Negeri 2 Torjun as evidenced by a value of 0.000 <0.05. With a correlation coefficient of determination of students' mental health of 2.56 in the weak category. It can be said that mental health has a weak relationship with PJOK learning outcomes.